An Inheritance Mode of Rural Cultural Heritage Based on Virtual Museum in China. (6th August 2021) - Yang, Yuhui; Zhang, Hao; Chen, Mo; Jiang, Youbin; Chai, Huifang
Abstract : In China, there is a crisis of rural cultural heritage inheritance due to urbanization. The traditional cultural inheritance modes such as building museums may not satisfy the needs of wide and fast culture transmission, communication, and inheritance. However, the virtual museum may provide new solutions. Nowadays, China has essential social-economic conditions for virtual museum construction but lacks sustainable modes for virtual museums supporting rural cultural heritage inheritance. In this study, we adopted the theoretical analysis method, expert argumentative method, and combined with virtual museum technology analysis to design an appropriate mode for the cultural heritage's inheritance in rural areas. We built a demonstrational virtual museum for the Mt. Mogan government according to this mode, adopted a comparative analysis and questionnaire survey to verify, and assess the application effects of the mode. Results show that the inheritance mode of rural cultural heritage based on the virtual museum has advantages of larger exhibition scale and wider scope of cultural transmission and communication with less input, and this mode's operation is steady and sustainable. The inheritance crisis of rural cultural heritage needs reasonable solutions, and our results can be a guideline for building virtual museums in rural areas to promote wide, fast, and sustainable cultural inheritance.